Motivating Factors for the Transfer of Information Literacy Skills among Undergraduates (Teaching and Learning Inquiry, 2022)
Faculty and academic librarians who provide information literacy (IL) instruction frequently puzzle over students’ inconsistent future use of IL skills. When they work with students who have received IL instruction in the past, some students demonstrate confident, mature, and practiced use of the skills. Others demonstrate skills that have either failed to develop further since the instruction session or skills that have atrophied. This study explores self-cited motivating factors for continued use of IL skills. It was conducted at an urban public research university in the United States, among 24 first- year undergraduates who participated in first-year seminars. The study connects the motivating factors with IL performance on a writing sample. It uses mixed methods involving a self-designed survey with Likert-style questions on eighteen motivating factors, plus a rubric adapted from the AAC&U VALUE rubrics.